Production and functional stability of the biourfactant isolated from Stenotrophomonas maltophilia UCP 1601 (Research, Society and Development, 2022)
The present study investigated the production of biosurfactant by Stenotrophomonas maltophilia UCP 1601under submerse fermentation using renewable substrates as carbon and nitrogen sources applying two statistical tools as Plakket-Burman experimental design and full factorial design to optimize the bioprocess. A partial characterization was performed by measuring the surface tension, emulsification index, determination of CMC, ionic charge. The biosurfactant was tested to different conditions of temperature, pH and salinity, in order to evaluate the stability of the biomolecule. The surface tension of the biosurfactant produced using corn steep liquor and glycerol was 27 mN/m, whose yield was 12.6 g/L, and its character is anionic. The critical micelle concentration (CMC) was 70% using the cell-free metabolic liquid. The biosurfactant was able to emulsify 56% of the burned engine oil. The biomolecule showed high functional stability and performance under extreme conditions of thermal, pH and saline concentrations stability. All determinations carried out confirm the generation of a stable, efficient bioproduct that contributes to the circular bioeconomy and the great potential for remediation under harsh environmental conditions.